European Society of Cardiology: cardiovascular disease statistics 2021. (8th January 2022) - Timmis (Chair Writing Group), Adam; Vardas, Panos; Townsend, Nick; Torbica, Aleksandra; Katus, Hugo; De Smedt, Delphine; Gale, Chris P.; Maggioni, Aldo P.; Petersen, Steffen E.; Huculeci, Radu; Kazakiewicz, Dzianis; de Benito Rubio, Victor; et al.
Abstract: Aims: This report from the European Society of Cardiology (ESC) Atlas Project updates and expands upon the widely cited 2019 report in presenting cardiovascular disease (CVD) statistics for the 57 ESC member countries. Methods and results: Statistics pertaining to 2019, or the latest available year, are presented. Data sources include the World Health Organization, the Institute for Health Metrics and Evaluation, the World Bank, and novel ESC sponsored data on human and capital infrastructure and cardiovascular healthcare delivery. New material in this report includes sociodemographic and environmental determinants of CVD, rheumatic heart disease, out-of-hospital cardiac arrest, left-sided valvular heart disease, the advocacy potential of these CVD statistics, and progress towards World Health Organization (WHO) 2025 targets for non-communicable diseases. Salient observations in this report: (i) Females born in ESC member countries in 2018 are expected to live 80.8 years and males 74.8 years. Life expectancy is longer in high income (81.6 years) compared with middle-income (74.2 years) countries. (ii) In 2018, high-income countries spent, on average, four times more on healthcare than middle-income countries. (iii) The median PM2.5 concentrations in 2019 were over twice as high in middle-income ESC member countries compared with high-income countries and exceeded the EU air quality standard in 14 countries, all middle-income. (iv) In 2016, more than one in five adults across the ESC member countries were obese with similar prevalence in high and low-income countries. The prevalence of obesity has more than doubled over the past 35 years. (v) The burden of CVD falls hardest on middle-income ESC member countries where estimated incidence rates are ∼30% higher compared with high-income countries. This is reflected in disability-adjusted life years due to CVD which are nearly four times as high in middle-income compared with high-income countries. (vi) The incidence of calcific aortic valve disease has increased seven-fold during the last 30 years, with age-standardized rates four times as high in high-income compared with middle-income countries. (vii) Although the total number of CVD deaths across all countries far exceeds the number of cancer deaths for both sexes, there are 15 ESC member countries in which cancer accounts for more deaths than CVD in males and five-member countries in which cancer accounts for more deaths than CVD in females. (viii) The under-resourced status of middle-income countries is associated with a severe procedural deficit compared with high-income countries in terms of coronary intervention, ablation procedures, device implantation, and cardiac surgical procedures. Conclusion: Risk factors and unhealthy behaviours are potentially reversible, and this provides a huge opportunity to address the health inequalities across ESC member countries that are highlighted in this report. It seems clear, however, that efforts to seize this opportunity are falling short and present evidence suggests that most of the WHO NCD targets for 2025 are unlikely to be met across ESC member countries. Graphical Abstract: Graphical Abstract This 2021 report from the ESC Atlas Project provides contemporary cardiovascular disease (CVD) statistics for 57 ESC member countries. It builds on the 2017 and 2019 reports with presentation of new data on sociodemographic and environmental determinants of CVD. Huge inequalities in disease burden persist between high-income and middle-income ESC member countries and across all member countries evidence suggests that most of the World Health Organization noncommunicable disease targets for 2025 are unlikely to be met. Advocacy to increase awareness of policy makers, members of the public and other stakeholders about the continuing importance of CVD as the leading cause of death among ESC member countries is a responsibility for all who are involved in cardiovascular research and healthcare.